Event Study on Declaration of Separation on Stock Prices of Hero MotoCorp Ltd. : A Case Study on Hero & Honda Separation - Tripathi, Abhishek; Singh, Amandeep (Indian Journal of Finance, 2012)
The event study methodology has been used to estimate cumulative average abnormal returns (CAR) in a 90 day window period (CAR) in a 1-day, 2-day, 5-day, 10-day, 15-day, 20-day, and 90-day window period of Declaration of Separation on stock prices of Hero Motor Corp. The study aims at exploring the implications of the separation for the shareholders. The event study methodology has been used to estimate Cumulative Abnormal Returns (CAR) for a 90 day window period. Market Model Method (single- factor model) has been used. This procedure has been applied on the Hero&Honda separation event so as to study the impact of this event on the stock prices. The study endeavours to find the Cumulative Abnormal Return (CAR) of Hero Moto Corp and analyzes the after effects of Hero&Honda Separation.